Soil edaphic condition in peat affecting the growth peformance of sago palm - Yong, Roland Chiew Ming (Universiti Malaysia Sarawak, (UNIMAS), 2014)
Sago palms (Metroxylon spp.) planted on shallow and deep peat, adhering to" good agricultura. practice showed good growth performance at early stage of its development i.e. less than 4 years after planting (Fariza, 2008). However, several researchers have reported that the characteristics of peat soils play an important role in the period for development of growth of sago palm. It has been reported that the trunking stage of sago palm cultivated in deep peat soils begins to deteriorate after few years ofcultivation due to high incidences oftapering mother palm and poor growth of succession palms. Moreover, sago cultivated in deep peat soils exhibited distinct elemental deficiency symptoms in the leaves which correspond likely due to inefficiency of nutrient uptake after fertilizer apPlicatioy It is evitable that soil properties play an important role in determining the growth performance of sago in peat area which later affects the growth pattern of sago palms. A preliminary study was conducted at Sebakong Sago Plantation (SSP), Mukah and Sungai Talau Research Station (STRS), Datat in order to identify the effect of soil phy icochemical properties that contributed to the growth performance in terms of trunking fonnation of sago palm. The study also involved in determining the inter relationship between characteristics ofthe peat soil in relation with the root distribution ofcultivated sago palm within the study area. Based on the initial findings, although soil physicochemical properties provide significant relationship with the growth pattern of cultivated sago palm, it was distinctive that the growth performance in term of the trunking formatioQ of sago palm cultivated in shallow peat and mineral soil are better than those cultivated in deep peat soils. Moreover, the decomposition rate in the peat soils plays an important role in determining the growth performance ofcultivated sago palm. It was observed that the peat soils with sapric-hemic-fibric conditions and with low percentage of undecomposed woody materials promote better condition rooting medium, anchorage and efficient adsorption as compared to fibric peat soils which is very raw and dominant with woody residues.